Experimental Study of Strain Rockburst considering Temperature Effect: Status-of-the-Art and Prospect - Lei Xu; Fengqiang Gong (Shock and Vibration)
In deep mining and excavation of tunnels with high geothermal, the surrounding rock is not only subjected to high ground stress but also subjected to high temperature. Temperature will change mechanical characteristics and energy storage capacity of rocks, as well as increase the destructiveness and randomness of rockburst. To reveal the mechanism of high-temperature strain burst in deep rock, the rockburst tests from uniaxial compression to three-dimensional compression were reviewed, and the research results of the minimum principal stress rapid unloading, true-triaxial loading with one free face, and dynamic disturbance triggered pre-heated granite rockburst simulation tests were focused on. According to the occurrence state of country rock for deep high-temperature and stress state in the whole process during excavation, six development directions for high-temperature strain rockburst simulation tests were proposed: (1) constructing the damage constitutive models of high-temperature rocks according to linear energy dissipation law; (2) developing the true triaxial rockburst simulation testing system accomplishing the function of “real-time high temperature + unloading + dynamic disturbance”; (3) considering the true triaxial rockburst simulation test after microwave irradiation; (4) developing the real-time high-temperature rockburst simulation testing device for large-size specimens and internal unloading; (5) focusing on the energy actuating mechanism for deep high-temperature rock failure via rockburst simulation tests; and (6) implementing the three-dimensional rockburst simulation test on the basis of deep in situ coring.